2020
DOI: 10.1101/2020.08.09.242933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The tolerance to hypoxia is defined by a time-sensitive response of the gene regulatory network in sea urchin embryos

Abstract: Deoxygenation, the reduction of oxygen level in the oceans induced by global warming and anthropogenic disturbances, is a major threat to marine life. Acute diurnal changes in oxygen levels could be especially harmful to vertebrate and sea urchin embryos that utilize endogenous hypoxia gradients to drive morphogenetic events during normal development. Here we show that the tolerance to hypoxic conditions changes between different developmental stages of the sea urchin embryo, due to the structure of the gene r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 66 publications
(134 reference statements)
0
7
0
Order By: Relevance
“…Thus, although the change in Vegf3 expression domain may be due to miR-1’s direct suppression, our results indicate that the expression of Vegf3 in the ventral-dorsal axis may be a result of miR-1’s direct regulation of Nodal . Additionally, a previous study has shown that a loss of Bmp2/4 resulted in the position of the PMC ring to shift towards the animal pole and a radialized the embryo (Angerer et al, 2000; Layous, 2020). Interestingly, in miR-1 mimic-injected gastrulae, we observed mispatterned PMCs that migrated near the animal pole (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Thus, although the change in Vegf3 expression domain may be due to miR-1’s direct suppression, our results indicate that the expression of Vegf3 in the ventral-dorsal axis may be a result of miR-1’s direct regulation of Nodal . Additionally, a previous study has shown that a loss of Bmp2/4 resulted in the position of the PMC ring to shift towards the animal pole and a radialized the embryo (Angerer et al, 2000; Layous, 2020). Interestingly, in miR-1 mimic-injected gastrulae, we observed mispatterned PMCs that migrated near the animal pole (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Both Nodal and Bmp2/4 signaling pattern the PMCs by restricting Vegf3 expression to the two lateral ectodermal domains and posterior ventral corners where the PMC clusters reside to form the skeletal rudiments within the border ectoderm-dorsal ventral margin (BE-DVM) intersection (Fig. 12A) (Duboc et al, 2010; McIntyre et al, 2013; Layous, 2020). In the ventral ectoderm, Nodal activates the expression of itself, Not1, Bmp2/4 and Vegf3 at 8-9 hpf in the ventral ectoderm (Lapraz et al, 2009; Li et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, S. unipunctata was able to increase the relative expression of the VEGF gene (Figure 7b), which is demonstrated to be involved in sea urchin spiculogenesis [50]. However, recent data on sea urchin gene regulatory networks (GRN) reported that hypoxia-induced stress is able to perturb the expression of HIF1A, nodal and VEGF pathways, inducing severe effects on the structure of larval skeletons [51]. This is also the case with our results, reporting a significant variation of these latter genes following diatom feeding, that might explain the anomalies in sea urchin plutei observed under light microscopy (Figure 1; see also Figure S3).…”
Section: Figurementioning
confidence: 91%